Emotional intelligence and transformational leadership behaviours of construction project managers. Issue 1 (3rd April 2018) - Potter, Emily M.; Egbelakin, Temitope; Phipps, Robyn; Balaei, Behrooz
Abstract : Purpose: Existing research has highlighted the need for influential leaders to respond to the evolving social, economic and environmental constraints on the construction industry. Studies on leadership in other sectors have shown that influential leaders tend to demonstrate a high level of emotional intelligence. Little or no research examining relationships between leadership style and emotional intelligence has been conducted specific to construction project managers. This study aims to identify the prevalent leadership style adopted by construction project managers and investigate potential correlations between leadership style and emotional intelligence. Design/methodology/approach: An online questionnaire including a mix of open and closed questions was adopted to address the research objectives. The group studied comprised project managers currently working in the construction industry in New Zealand and the UK. Findings: The research found that transformational leadership style is prevalent among project managers examined in this study. Significant positive relationships were found between project managers' emotional intelligence and their likelihood of adopting a transformational leadership style. Originality/value: The research results provide the construction industry with a benchmark against which individuals with high emotional intelligence, and so most suited to the challenges of the project management role, can be identified and trained. Recommendations including suitable methods for identifying, recruiting and training project managers, as well as secondment and mentoring options, were suggested for improving leadership capabilities in the construction industry.